When reversing the order of $a_1$ through $a_n$ in a continued/extended fraction, (ie. [$a_1$: $a_2$, ... $a_{n-1}$, $a_n$] becomes [$a_n$: $a_{n-1}$, ... $a_2$, $a_1$]) we see that the denominator changes, but the numerator remains the same.

$a_1+\frac{1}{a_2+\frac{1}{...+\frac{1}{a_n}}}\\$ = $\frac{A}{B}$ $\Rightarrow$ $a_n+\frac{1}{...+\frac{1}{a_2+\frac{1}{a_1}}}\\$ = $\frac{A}{C}$

For example:

$2+\frac{1}{3+\frac{1}{4+\frac{1}{5}}}$ = $\frac{157}{68}$


$5+\frac{1}{4+\frac{1}{3+\frac{1}{2}}}$ = $\frac{157}{30}$

Is there a way to predict exactly how the denominator will change without simplifying to an improper fraction?


Most definitely. Steps:

  1. The following link proves the connection between the elements of a continued fraction and the elements produced by the euclidean algorithm: Show that the elimination of the successive remainders from the Euclidean algorithm leads to a finite expansion.

  2. Examine the following link, which establishes a common notation and (in its Example section) shows an easy way to calculate $p_1, p_2, ..., q_1, q_2, ...$ : https://crypto.stanford.edu/pbc/notes/contfrac/definition.html.

  3. Assume that $a_1, a_2, \cdots a_k$ are known and that $p_k,q_k$ are known. The following analysis proves that $[a_k; a_{k-1}, \cdots, a_1] = \frac{p_k}{p_{k-1}}.$ The problem therefore reduces to using the method in step 2 above to calculate $p_{k-1}.$

For $k=2, \frac{p_2}{p_1} = \frac{a_2 a_1 + 1}{a_1} = a_2 + \frac{1}{a_1} = [a_2;a_1].$

For $k>2,\;$ inductively assume that $\;[a_{k-1}; a_{k-2}, \cdots, a_1] = \frac{p_{k-1}}{p_{k-2}}.$

Thus, $\;p_k = a_k p_{k-1} + p_{k-2} \;\Rightarrow$
$\frac{p_k}{p_{k-1}} = a_k + \frac{p_{k-2}}{p_{k-1}} = a_k + \frac{1}{\frac{p_{k-1}}{p_{k-2}}} = [a_k; a_{k-1}, a_{k-2}, \cdots, a_1].$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.